Financial Conditions and CSR on the Financial Performance of Financial Firms - Randy Sanjaya; Arif Budi Satrio (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Firm financial performance is an essential topic in current research. This study aims to analyze the financial performance of financial firms in Indonesia from two perspectives: corporate social responsibility and financial condition. The analysis used a regression model on 95 firms for the 2019-2023 period. The results indicate that a firm's financial condition, specifically capital structure, negatively impacts profitability, while CSR has a positive effect. Conversely, liquidity has no proven role. Overall, the results of this study emphasize the importance of implementing CSR in supporting improved corporate financial performance and encourage further research to understand the complex relationship between liquidity and corporate profitability.